DESAIN LEMBAR KERJA MAHASISWA (LKM) BERBASIS PEDAGOGI HIJAU UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UR - Siti Sacharisa Ade Sami; Firdaus L.N '; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose this study was to design Student Worksheet (LKM) based Green Pedagogy. Research conducted at the campus of the Faculty of Sciences of Education University of Riau (Biologi FKIP UR) in January-June 2015. The LKM is designed to help students explore biology pre- teacher to understanding of the environment and sustainability to foster competence ESD biology teacher, LKM development is based on a 5-dimensional model of burn that content contains of LKM contained sustainability issues that context is local and close to the student. The issues raised trying to dig critically reflective abiding students to be able to think and act green through experiential learning and active participation in learning. Type this study was research and development by using ADDIE’s model. Instrument in this study were used observation sheets, interviews sheet, validation sheets and questionnaire responses sheets. The development of LKM was validation by 3 validator. Aspects assessed on LKM which aspects of design, pedagogy, and the content and language. There are 13of LKM based Pedagogy Green was develop, validation values showed that average score validation in the range of 3.06 to 3.19 with a valid category. Advice given validator for LKM serve as revision material prior to LKM before preliminary field test. preliminary field test held on 20 students of Biology Education. Based on student responses to the use of the LKM was excelent with obtained a score of 85.83% on aspects of design, 86.56% on aspects of pedagogy, and 85.50% on aspects of language and content.Keywords: Student Worksheet (LKM), Green Pedagogy, Education for Sustainable Development, Sustainable Issues.